2020
DOI: 10.1089/cell.2020.0022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Additional Cytoplasm of Cloned Embryo on In Vitro Developmental Competence and Reprogramming Efficiency in Mice

Abstract: Somatic cell nuclear transfer (SCNT) is an important technique for biological science research. Cytoplasm injection cloning technology (CICT) was developed to improve the reprogramming efficiency as well as to overcome the limitations of SCNT. CICT uses an additional cytoplasm fused with an enucleated oocyte to restore the cytoplasmic volume of the cloned embryo, and this method could improve the reprogramming efficiency of the cloned embryo. In this study, we show that CICT can be adapted to mouse species to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Similarly, in cloned mice, cytoplasmic supplementation improved the in vitro development and quality of cloned mouse embryos. Additionally, CICT-derived mouse embryos had a lower number of apoptotic cells and higher acetylation levels when compared with those of SCNT-derived embryos [77]. Notably, CICT significantly increased the birth rate of cloned cat embryos when compared to that of SCNT (4.8% and 0.7%, respectively) [78].…”
Section: Cytoplasmic and Mitochondrial Supplementation In Enucleated ...mentioning
confidence: 93%
“…Similarly, in cloned mice, cytoplasmic supplementation improved the in vitro development and quality of cloned mouse embryos. Additionally, CICT-derived mouse embryos had a lower number of apoptotic cells and higher acetylation levels when compared with those of SCNT-derived embryos [77]. Notably, CICT significantly increased the birth rate of cloned cat embryos when compared to that of SCNT (4.8% and 0.7%, respectively) [78].…”
Section: Cytoplasmic and Mitochondrial Supplementation In Enucleated ...mentioning
confidence: 93%
“…Nevertheless, the question of the reprogramming factor-to-DNA ratio seems to be rather complicated and conflicting results can be found in the literature: on one hand, some authors reported that increasing the amount of the reprogramming factors present by MII cytoplast fusion is not beneficial in terms of the SCNT efficiency outcomes (Sayaka et al 2008). On the other hand, others claimed that introducing extra cytoplasm to the cytoplasts leads to better developmental rates to the blastocyst and increased H3K9/K14 acetylation (Song et al 2020). At the same time, the hand-made cloning, during which the egg is bisected into two halves and the half lacking the spindle is used as recipient cytoplast, has been used with success in large animals; for review, see Verma et al 2015, Saini et al 2018 Although the reduced size cytoplasts are not typically used in the laboratory mouse, the hand-made cloning raises the question of whether the full content of cytoplast reprogramming and remodeling factors is indeed needed to achieve the SCNT success and whether the cytoplast impacts the transferred nucleus only in a positive manner.…”
Section: R83mentioning
confidence: 99%
“…The possibility to improve the quality of cloned mice with the SCNT technique has been developed and is very useful for biomedical research purposes as an experimental animal (Ogura, 2020). Song et al (2020) cloned mouse embryos by reprogramming the cloned embryos' cytoplasmic volume. Cytoplasm injection (CICT; cytoplasm injection cloning technology) was developed to increase reprogramming of the SCNT.…”
Section: E Bullmentioning
confidence: 99%